2020
DOI: 10.15578/squalen.v15i3.445
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Histamine-Producing Bacteria on Tuna Species using Histidine Decarboxylase (hdc) and 16S rRNA

Abstract: Histamine-producing bacteria to predict histamine level production can be identified by a molecular approach. The purpose of this study was to identify the types of histamine-producing bacteria on tuna, little tuna, and skipjack (TTC) meat, to analyze its bioinformatics through phylogenetic tree construction also to determine the levels of its histamine. The identification of histamine-producing bacteria was conducted using a molecular technique based on the hdc and 16S rRNA genes. Histamine levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
1
0
3
Order By: Relevance
“…1 Prosentase isolat positif hdc dihitung dari total koloni presumptif untuk setiap jenis ikan/Percentages of hdcpositive isolates were calculated from total number of presumptive colonies for each fish baik pada produk perikanan segar (Nurilmala et al, 2020) maupun olahan seperti pindang (Fatuni et al, 2014;Rachmawati, 2019).…”
Section: Screening Results Of Histamine Producing Bacteria (Hpb) From Tuna and Tuna-like Fishunclassified
See 1 more Smart Citation
“…1 Prosentase isolat positif hdc dihitung dari total koloni presumptif untuk setiap jenis ikan/Percentages of hdcpositive isolates were calculated from total number of presumptive colonies for each fish baik pada produk perikanan segar (Nurilmala et al, 2020) maupun olahan seperti pindang (Fatuni et al, 2014;Rachmawati, 2019).…”
Section: Screening Results Of Histamine Producing Bacteria (Hpb) From Tuna and Tuna-like Fishunclassified
“…Hal ini merupakan salah satu faktor penting yang diperlukan dalam studi atau kajian risiko histamin pada produk perikanan. Beberapa studi untuk mengetahui jenis BPH yang berperan dalam pembentukan histamin pada produk perikanan di Indonesia pernah dilakukan pada ikan olahan seperti pindang (Fatuni, Suwandi, & Jacoeb, 2014;Rachmawati, 2019), kembung peda (Indriati, Rispayeni, & Heruwati, 2006), serta beberapa komoditas TTC untuk ekspor yang telah mengalami proses penyimpanan pada suhu yang berbeda (Nurilmala et al, 2020;Wahyuni, 2011). Sementara itu, informasi terkait BPH pada TTC segar untuk konsumsi domestik masih sangat terbatas.…”
Section: Pendahuluanunclassified
“…Since it is not possible to analyze all these bacteria separately, both economically and practically, the numbers of genes responsible for the production of these biogenic amines were determined and this amount was compared with the classical microbiological analysis ndings and it was investigated whether or not this method could be used in food spoilage detection. Previous studies have shown that PCR or Real-time PCR methods have been generally used in the detection of these genes (Moniente et al 2021;Nurilmala et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sample tests were conducted to determine whether the marine ornamental fish samples are infected with VHSV or not [15]. The sample test is carried out by inserting 1μl of template into the master mix so that the final volume of the reaction is 12.5μl.…”
Section: Methodsmentioning
confidence: 99%